Family Economic Empowerment through Animal Husbandry Entrepreneurship Training - Badat Muwakhid; Djoko Subagyo (www.amertainstitute.com, 2026)
Family economic resilience in rural communities is closely associated with the capacity of households to develop productive and sustainable sources of income. However, many livestock farmers continue to face limitations in entrepreneurship, business management, financial administration, innovation, and marketing, which constrain the development of livestock enterprises. This community service program aimed to strengthen the motivation, knowledge, and practical skills of livestock farmers in developing competitive enterprises while contributing to family economic empowerment. The program was conducted at Songgokerto Village Hall, Batu City, East Java, Indonesia, from 6 to 8 June 2026, involving representatives of livestock farmers participating in the livestock-sharing program from several villages in Batu City. A participatory training approach was employed through lectures, interactive discussions, question-and-answer sessions, and a participatory forum. Training materials covered entrepreneurial motivation, entrepreneurial innovation, business management, financial administration, and marketing strategies for livestock products. The results indicated that participants demonstrated strong engagement and improved understanding of entrepreneurial characteristics, business planning and management, simple financial recordkeeping, product innovation, and livestock-product marketing strategies. Interactive discussions also enabled participants to share business experiences, identify operational constraints, and formulate potential solutions relevant to their local conditions. Overall, the training strengthened participants’ entrepreneurial and managerial capacities and provided practical knowledge for improving livestock business performance. Continuous mentoring and follow-up assistance are recommended to support the implementation of acquired competencies and enhance the sustainability of livestock enterprises and family economic resilience.